Étude structurelle du Décalogue selon Ex 20, 2-17 - Auffret, Pierre 1937-2018 (2014)
Tenant compte des propositions de Claude Wiener, André Wénin et Roland Meynet, l'auteur reprend ici l'étude structurelle du Décalogue selon la version d'Ex 20, et cela le plus méthodiquement possible, c'est-à-dire en considérant d'abord la structure de chaque unité, puis, peu à peu, celle de l'ensemble. Il s'avère finalement que ce dernier s'ordonne concentriquement autour du commandement sur le sabbat, ou selon un chiasme dont les termes centraux seraient chacun des deux volets du commandement sur le sabbat. On perçoit alors avec plus de netteté l'importance de l'articulation fondamentale entre les commandements et ce qui les motive.
The author resumes a structural analysis of the Decalogue as it is found in Exod 20, while taking into consideration the proposals made by Claude Wiener, André Wénin and Roland Meynet. The investigation is undertaken as methodically as possible, that is to say, first investigating the structure of each unit on its own and then, little by little, that of the whole composition. The result reveals that the text is organised concentrically around the commandment about the Sabbath, thus in the form of a chiastic arrangement where the central terms are taken from the two branches of the commandment about the Sabbath. This reveals more clearly the importance of the fundamental relationship between the commandments and what motivates them.
Keywords: Decalogue; Exodus; Sabbath